A case report of uterine rupture after repeated conservative treatment for adenomyosis - Jae Young Kwack; Yong-Soon Kwon; Kyong Shil Im; Hyeyoon Jeong; Youngeun Lee (IMR Press, 2022)
Background: Among the pregnancy complications after an adenomyomectomy, uterine rupture is fatal for both the mother and baby. There have been a few reports of uterine rupture during pregnancy related to adenomyosis or adenomyomectomy. Case: A 34-year-old nulliparous woman with abdominal discomfort at 27 weeks of gestation visited our clinic. She had a history of complex treatments for symptom relief and fertility for uterine adenomyosis, which included repeat adenomyomectomies and high-intensity focused ultrasound (HIFU). Three months after her last adenomyomectomy, she conceived by in vitro fertilization. During antenatal care at our clinic at 27 weeks of gestation, the results of an examination for abdominal discomfort with focal tenderness on the lower abdomen was suspicious for uterine rupture and fetal distress. An emergency cesarean delivery was performed. The mother's uterus was repaired without significant postoperative complications and the neonate was admitted to the intensive care unit for prematurity care and presently is well. Conclusions: During antenatal care of a pregnant woman with a history of adenomyosis treatment, heightened awareness of catastrophic pregnancy-related complications should be maintained to obtain the best maternal and fetal outcomes.